Trouble dans le positivisme, la création en tant que recherche : le cas de La zona del silencio - Pageot, Édith-Anne (RACAR : Revue d'art canadienne / Canadian Art Review, 2023)
This article proposes to study research-creation by considering our embodied relationship to the world. It is an approach that tends to reject the ontological distance implied by positivism. Often subversive, research-creation itself blurs disciplinary thresholds and undermines positivist logic. The lesser-known La zona del silencio collective project, set up in the Mexican desert between 1984 and 1985, bought together twelve artists with diverse disciplinary backgrounds from Mexico, Germany, Canada, and the Cree Nation. The environmental complexity of the site, the transnational dimension of the project and the cultural plurality of the group incited the artists to connect and to form a community. La zona del silencio offers an alternative vision of contemporary art that can be compared to Arturo Escobar’s concept of sentipensar con la tierra and that, in some ways, resonates with the words of Édouard Glissant. This case study demonstrates how research-creation has a disruptive and transformative potential.